2007
DOI: 10.1128/aem.02219-06
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Real-Time PCR Assays for the Detection of Emetic Bacillus cereus Strains in Foods and Recent Food-Borne Outbreaks

Abstract: Cereulide-producing Bacillus cereus can cause an emetic type of food-borne disease that mimics the symptoms provoked by Staphylococcus aureus. Based on the recently discovered genetic background for cereulide formation, a novel 5 nuclease (TaqMan) real-time PCR assay was developed to provide a rapid and sensitive method for the specific detection of emetic B. cereus in food. The TaqMan assay includes an internal amplification control and primers and a probe designed to target a highly specific part of the cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
147
1
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(156 citation statements)
references
References 39 publications
1
147
1
7
Order By: Relevance
“…Although Fricker et al 2007 andWehrle et al 2010 used multiplex real-time PCR assays to simultaneously detect different enteropathogenic bacteria, simplex real-time PCR assays based on TaqMan probe and SYBR green I could be used for the rapid and conclusive identification of emetic type strains among B. cereus isolates, as well as some selective agar media normally utilized for isolation of foodborne B. cereus. However, the enrichment of foods contaminated with the level of 10 0 cfu/g was required for the assays.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Fricker et al 2007 andWehrle et al 2010 used multiplex real-time PCR assays to simultaneously detect different enteropathogenic bacteria, simplex real-time PCR assays based on TaqMan probe and SYBR green I could be used for the rapid and conclusive identification of emetic type strains among B. cereus isolates, as well as some selective agar media normally utilized for isolation of foodborne B. cereus. However, the enrichment of foods contaminated with the level of 10 0 cfu/g was required for the assays.…”
Section: Figmentioning
confidence: 99%
“…Primers and probes Table 1 designed by Fricker et al 2007 , targeting a region of the ces genes, were synthesized by Life Technologies Japan TM and used for conventional PCR and real-time PCR assays.…”
mentioning
confidence: 99%
“…cereus is undervalued as a foodborne pathogen, despite the fact that, it has been implicated in various foodborne outbreaks worldwide (Bennett et al, 2013) and this could be attributed to the lack of effective surveillance, underreporting of B. cereus linked food poisoning, and cases of B. cereus food poisoning apparently confused with Staphylococcus aureus and Clostridium perfringens food poisoning due to comparable symptoms (Fricker et al, 2007;StenforsArnesen et al, 2008), finally, B. cereus is not taken in account when diarrhea cases are diagnosed even if the fecal samples gave negative results for the presence of Salmonella, Shigella and Entamoeba in the middle east (Organji et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Fricker et al, (2007) reported on the successful application of real-time PCR in the detection of B. cereus, which together with the closely associated S. aureus are the two most important bacteria responsible for food-associated intoxications. The traditional detection of the emetic toxin associated with these bacteria is often difficult, time consuming and expensive.…”
Section: Pcr-based Food -Borne Pathogen (Bacteria) Detectionmentioning
confidence: 99%